Natural History of Myocardial αvβ3 Integrin Expression After Acute Myocardial Infarction : Correlation with Changes in Myocardial Blood Flow - Dietz, Matthieu (Society of Nuclear Medicine, 2025)
Angiogenesis is an essential part of the cardiac repair process after myocardial infarction, but its spatiotemporal dynamics remain to be fully deciphered.68Ga-NODAGA-Arg-Gly-Asp (RGD) is a PET tracer targeting αvβ3 integrin expression, which is a marker of angiogenesis. Methods: In this prospective single-center trial, we aimed to monitor angiogenesis through myocardial integrin αvβ3 expression in 20 patients with ST-segment elevation myocardial infarction (STEMI). In addition, the correlations between the expression levels of myocardial αvβ3 integrin and the subsequent changes in 82Rb PET/CT parameters, including rest and stress myocardial blood flow (MBF), myocardial flow reserve (MFR), and wall motion abnormalities, were assessed. The patients underwent 68Ga-NODAGA-RGD PET/CT and rest and stress 82Rb-PET/CT at 1 wk, 1 mo, and 3 mo after STEMI. To assess 68Ga-NODAGA-RGD uptake, the summed rest 82Rb and 68Ga-NODAGA-RGD images were coregistered, and segmental SUVs were calculated (RGD SUV). Results: At 1 wk after STEMI, 19 participants (95%) presented increased 68Ga-NODAGA-RGD uptake in the infarcted myocardium. Seventeen participants completed the full imaging series. The values of the RGD SUV in the infarcted myocardium were stable 1 mo after STEMI (1 wk vs. 1 mo, 1.47 g/mL [interquartile range (IQR), 1.37-1.64 g/mL] vs. 1.47 g/mL [IQR, 1.30-1.66 g/mL]; P = 0.9), followed by a significant partial decrease at 3 mo (1.32 g/mL [IQR, 1.12-1.71 g/mL]; P = 0.011 vs. 1 wk and 0.018 vs. 1 mo). In segment-based analysis, positive correlations were found between RGD SUV at 1 wk and the subsequent changes in stress MBF (Spearman ρ: r = 0.17, P = 0.0033) and MFR (Spearman ρ: r = 0.31, P < 0.0001) at 1 mo. A negative correlation was found between RGD SUV at 1 wk and the subsequent changes in wall motion abnormalities at 3 mo (Spearman ρ: r = -0.12, P = 0.035). Conclusion: The present study found that αvβ3 integrin expression is significantly increased in the infarcted myocardium 1 wk after STEMI. This expression remains stable after 1 mo and partially decreases after 3 mo. Initial αvβ3 integrin expression at 1 wk is significantly weakly correlated with subsequent improvements in stress MBF, MFR, and wall motion analysis.